Bringing Science to Life: STEM-Based Instructional Strategies for Primary Students in Thailand - Kuaemilia Nitae; Prasart Nuangchalerm; Roswanna Safkolam (Online Learning In Educational Research (OLER), 2025)
Many students in Grade 5 struggle to make sense of science lessons, especially when the material feels abstract and far from their everyday experience. Although science holds an important place in Thailand’s education system as one of the eight main subjects, young learners often find it difficult to stay engaged or fully grasp the concepts. STEM education, a contemporary and productive instruction to science.This study aimed to investigate the implementation of STEM-based science learning activities for Grade 5 students in terms of learning outcomes and student satisfaction. The one group pre-test and post-test design was employed. This study involved eight Grade 5 students who were chosen through purposive sampling. They took part in a series of STEM-based science lessons, with data gathered through lesson plans, achievement tests, and a student satisfaction questionnaire. The results showed a significant improvement in post-test scores compared to pre-test scores, and student satisfaction was rated at the highest level (M = 4.79, SD = 0.34). These findings highlight the potential of STEM-based instruction to improve learning outcomes and engagement in primary science education